La familia peruana en el contexto global: Impacto de la estructura familiar y la natalidad en la economía del mercado - Huarcaya, Gloria (Mercurio Peruano, 2020)
Has the family some connection to the Economy? The present article comments on the most relevant topics from the SDD Report (2011), an international study which analyzes the structure, economy, welfare and culture of families from 29 countries in all regions; and contributes to a better understanding of the roles that family stability and fertility play in socioeconomic development. The global crisis seems to have a demographic background, and the high rates of family instability in Latin America have had a significant impact on underdevelopment; so the policies that encourage fertility and family stability are so recommended from the economic perspective.